MODEL PEMBELAJARAN TEMATIK TERPADU - nazar . (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Thematic learning is a learning model that is packaged in the form of themes involving several subjects that are presented in an integrated system. The application of integrated thematic models began in the 1970s. In the Education United Level Curriculum is applied to students in class I to clas III, and in the 2013 Curriculum the overall application, starting from class I to class VI by linking subjects in an integrated thematic learning theme applied